2012
DOI: 10.18388/abp.2012_2138
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and medical importance of vanadium compounds.

Abstract: Vanadium belongs to the group of transition metals and is present in the air and soil contaminants in large urban agglomerations due to combustion of fossil fuels. It forms numerous inorganic compounds (vanadyl sulfate, sodium metavanadate, sodium orthovanadate, vanadium pentoxide) as well as complexes with organic compounds (BMOV, BEOV, METVAN). Depending on the research model, vanadium compounds exhibit antitumor or carcinogenic properties. Vanadium compounds generate ROS as a result of Fenton's reaction or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 65 publications
1
107
0
4
Order By: Relevance
“…Prediction of the in vivo effect of these compounds is not straightforward as their interactions with enzymes disseminates to so many distinct systems and at so many levels of the cell cycle [31].…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Prediction of the in vivo effect of these compounds is not straightforward as their interactions with enzymes disseminates to so many distinct systems and at so many levels of the cell cycle [31].…”
Section: Final Remarksmentioning
confidence: 99%
“…However, the complexity of their effects and the lack of knowledge in some areas such as their effects on e.g. the immune systems and inflammatory processes, or in their use in long-term administration therapies, and of the risks associated with their potential carcinogenic effect and disorders in the free-radical background in cells, require a much deeper understanding and evaluation of the balance between beneficial and toxic effects of their use [31].…”
Section: Final Remarksmentioning
confidence: 99%
“…Evidences from in vivo and in vitro studies have demonstrated that vanadium compounds exert various insulin-mimetic properties [24][25][26][27][28] and anti-diabetic effects [29][30][31][32][33]. These include their ability to improve glucose homeostasis and insulin resistance in animal models of type 1 and type 2 diabetes mellitus [34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Progress in the chemistry of vanadium related to the search of therapeutic applications has been exponential during the last 10-15 years, and several reviews have been published, a few of them during the last five years [1,62,[173][174][175][176][177][178][179][180][181][182][183].…”
Section: Prospective Application Of Vanadium Compounds In Therapeuticsmentioning
confidence: 99%
“…While this potentiates their application in therapeutics, namely the treatment of diabetes, it may also exert nonspecific opposite effects on several cell functions. Moreover, still not much is known regarding global toxicity issues and effects of vanadium on the immune system and inflammatory reactions, particularly if long-term administration is required [181]. Namely vanadium-induced oxidative stress [196][197][198] is probably a major factor, namely at the level of the mitochondria.…”
Section: Insulin-like Effects Of Vanadium Compoundsmentioning
confidence: 99%